You can't stay here forever : a novel - Lin, Katherine (Harper, an imprint of HarperCollinsPublishers, 2023)
"After the death of her husband, Ellie Huang, discovering he had a mistress, cashes in his life insurance policy for an extended stay on the French Riviera with her best friend--a sun-drenched getaway that turns into a reckoning for Ellie as long-simmering tensions and uncomfortable truths come to the surface"--